Ehkäisevä päihdetyö Suomessa 2011 : missä mennään, minne haluamme? - Strand, Teija (Raportti / Terveyden ja hyvinvoinnin laitos, ISSN 1798-0070, 2011)
Abstract: Substance abuse prevention in Finland 2011 : where are we now? Where do we take it from here?
Keywords: Alcoholism : prevention & control; Community Networks; Cooperative Behavior; Goals; Health Planning; Preventive Health Services; Preventive Health Services : organization & administration; Preventive Health Services : trends; Substance-Related Disorders : prevention & control; alueellinen yhteistyö; ehkäisevä päihdetyö; förebyggande missbruksarbete; koordinering; koordinointi; nykterhetsarbete; päihdetyö; raittiustyö; regionalt samarbete; rusmedelsarbete